Studi Penanggulangan Banjir Datuk Laksamana Dumai - Juliswan, Arif; Siswanto, Siswanto; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One of the disaster in Dumai City is a flood. This study tries to solve the problem by using a pump. In order to the pump can be able to function with optimally, it is necessary to be given temporary ponds reservoirs. The reservoirs is used to . Case study area observed is Simpang Tetap street. this study conducted a simulati accommodate the water discharge temporary before it is flow to drainage waster with pump support. The location in this study is Jalan Datuk Laksamana. In this research perform reservoirs simulation and pump, to alternate flood prevention. The discharge had been calculated by Rational method and IDF curve by Mononobe method. Ponds reservoirs sized 15000 m3(100m x 50m x 3m) requires pumping capacity of 1 m3 / sec to handle the floodwaters. So a pump 1m3 / sec can be to pump of water from ponds reservoirs to the Dumai River as channel waster.Keywords: flood, drainage system, ponds reservoirs, pumps